A cross-cultural study of religiosity and tax compliance attitudes in Malaysia and Turkey - Mohdali, Raihana; Benk, Serkan; Budak, Tamer; Isa, Khadijah; Yussof, Salwa Hana (School of Taxation and Business Law (Atax), UNSW Business School UNSW Australia, 2017)
Ensuring compliance in tax collection is very crucial as tax is one of the basic elements of public financing in almost all countries. The issue of compliance in tax research has been explored over many years from different perspectives. Initially, it started with a negative assumption of taxpayers’ compliance attitudes and recently the research has shifted to a more positive attitude of taxpayers. One of the factors that is expected to shape taxpayers’ compliance attitudes is religiosity. Even though a number of studies have started to explore this issue recently, not many studies have used primary data because the majority of the studies were relying on secondary data. Therefore, this study is comparing the impact of religiosity and its components on both tax compliance components, voluntary and enforced tax compliance, in Malaysia and Turkey. Surveys distributed to individual taxpayers were used in both countries. Religiosity is found to have a significant impact on voluntary tax compliance that influences taxpayers’ positive attitudes in both countries. Even though religiosity seems to be an influential factor with respect to tax compliance behaviour, this study has shown that in certain circumstances, it might appear irrelevant.